Nursing Leadership and COVID-19:: Defining the Shadows and Leading Ahead of the Data - Wymer, Joshua A; Stucky, Christopher H; De Jong, Marla J (Nurse leader, 2021)
The COVID-19 pandemic overwhelmed health care systems and exposed major gaps in preparedness and response plans. The crisis challenged nurse leaders to develop and implement novel care delivery plans while preventing disease transmission to patients and staff. COVID-19 required nurse leaders to make decisions in an environment of conflicting data and directives. The authors share essential nurse leader competencies vital to the development and support of thriving nurse leaders. As crises persist and future challenges arise, nurse leaders can leverage these essential competencies to successfully drive engagement, lead ahead of consensus, and define the shadows of limited, incomplete, and conflicting data.The COVID-19 pandemic overwhelmed health care systems and exposed major gaps in preparedness and response plans. The crisis challenged nurse leaders to develop and implement novel care delivery plans while preventing disease transmission to patients and staff. COVID-19 required nurse leaders to make decisions in an environment of conflicting data and directives. The authors share essential nurse leader competencies vital to the development and support of thriving nurse leaders. As crises persist and future challenges arise, nurse leaders can leverage these essential competencies to successfully drive engagement, lead ahead of consensus, and define the shadows of limited, incomplete, and conflicting data.